L-carnitine supplementation to prevent postoperative complications after cardiac surgery: A systematic review and meta-analysis of randomised clinical trials - Laila Shalabi; Ahmed Ibrahim; Mohamed Adel Elsawy; Sofian Zreigh; Muhiddin Dervis; Mohamed N. Elshabrawi; Sohaila Mourad; Mohamed A. Arafa; Mohamed Abuelazm (Indian Journal of Anaesthesia)
Background and Aims: Cardiac surgeries often lead to postoperative complications, which affect recovery and increase morbidity and mortality. This systematic review aims to assess L-carnitine’s effect on preventing postoperative complications across various cardiac surgeries, addressing gaps in current literature on its potential therapeutic benefits. Methods: We systematically searched Web of Science, Cochrane, Embase, PubMed, and Scopus databases until March 2025. Statistical analysis was performed using R version 4.3.2. Effect sizes were measured with relative risks (RR) for dichotomous outcomes and mean differences (MD) for continuous outcomes, while heterogeneity was evaluated using the I² statistic. Results: Thirteen randomised controlled trials(RCTs) with 786 patients were included. L-carnitine significantly increased the cardiac index (CI) (MD: 0.14; 95% CI: 0.07, 0.20; P < 0.01) and left ventricular stroke work index (LVSWI) (MD: 0.42; 95% CI: 0.06, 0.78; P = 0.02). In addition, L-carnitine significantly improved the left ventricular ejection fraction (LVEF) (MD: 7.88; 95% CI: 6.67, 9.09; P < 0.01), with a significant reduction in postoperative atrial fibrillation (POAF) (RR: 0.53; 95% CI: 0.30, 0.95; P = 0.03). In contrast, there was no significant reduction in in-hospital mortality (RR: 0.51; 95% CI: 0.10, 2.63; P = 1.00) and stroke incidence (RR: 0.85; 95% CI: 0.12, 5.76; P = 0.82). Conclusion: Preoperative administration of L-carnitine demonstrates meaningful short-term benefits in enhancing CI, LVSWI, and LVEF while reducing the incidence of POAF following cardiac surgery. These findings suggest a potential role for L-carnitine supplementation in optimising perioperative cardiac care, enhancing recovery, and reducing complications following cardiac surgery. However, the existing studies are limited in scope, making it challenging to draw robust conclusions.